Acid external and internal environment exchange the Oreochromis niloticus tissue immune gene expression compared to the mouse macrophage polarization model - Pan, Po-Kai; Wu, Tsung-Meng; Tsai, Hsin-Yuan; Cho, I-Cheng; Tseng, Hsin-Wei; Lin, Tai-Du; Nan, Fan-Hua; Wu, Yu-Sheng (Frontiers in Immunology, 2022)
The water environment plays an important role in animal physiology. In this study, we sought to evaluate the effect of the acid environment on the Oreochromis niloticus (Nile tilapia) internal microenvironment immune response compare to the mouse macrophage model (J77A.1). The acid environment treated mouse macrophage J774A.1 model have shown that acidic treatment is able to polarize macrophages into M2-like macrophages via an increase in Ym1, Tgm2, Arg1, Fizz1, and IL-10 expression. Metabolic analysis of mouse macrophages (J774A.1) at pH 2 vs. pH 7 and pH 4 vs. pH 7 have been shown to promote the expression of intracellular acetylcholine, choline, prochlorperazine, L-leucine, and bisphenol A,2-amino-3-methylimidazo[4,5-f] quinolone metabolites in the M2-like macrophage. Immune gene expression of the O. niloticus spleen and liver treated at pH 2, 4, and 7 was shown to reduce TNF-α, IL-1 β, IL-8, and IL-12 expression compared to pH 7 treatment. Immune gene was induced in O. niloticus following culture at pH 5, 6, and 7 fresh water environment. Taken together, we found that the acid internal environment polarizes tissues into an M2 macrophage developmental microenvironment. However, if the external environment is acid, tissues are exposed to an M1 macrophage developmental microenvironment.